2020
DOI: 10.5483/bmbrep.2020.53.7.253
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl flavones from Humulus japonicus suppress MMP-1 production via decreasing oxidative stress in UVB irradiated human dermal fibroblasts

Abstract: Exposure to Ultraviolet (UV) light induces photoaging of skin, leading to wrinkles and sunburn. The perennial herb Humulus japonicus, widely distributed in Asia, is known to have antiinflammatory, antimicrobial, and antioxidant effects. However, the physiological activities of isolated compounds from H. japonicus have rarely been investigated. This study focused on the isolation of active compounds from H. japonicus and the evaluation of their effects on photoaging in UVB-irradiated human fibroblast (Hs68) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Similarly, UVB-damaged fibroblasts were improved by several polyphenols [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] ( Table 1 ). Baicalin, delphinidin, ellagic acid (EA), fisetin, isoorientin, genistein, and luteolin increased the expression levels of collagen I and III, whereas it decreased the expression levels of MMP-1 and MMP-3 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Interestingly, baicalin had no difference in the normal fibroblasts without UVB irradiation [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, UVB-damaged fibroblasts were improved by several polyphenols [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] ( Table 1 ). Baicalin, delphinidin, ellagic acid (EA), fisetin, isoorientin, genistein, and luteolin increased the expression levels of collagen I and III, whereas it decreased the expression levels of MMP-1 and MMP-3 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Interestingly, baicalin had no difference in the normal fibroblasts without UVB irradiation [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, apigenin treatment of skin fibroblasts strongly promoted the elevation of AO-related proteins, Nrf2, and HO-1 in a dose-and time-dependent manner. The study further revealed that the extract suppressed the UVB-induced MMP-1 production by inhibiting the phosphorylation of the MAPKs and AP-1 [297]. Moreover, apigenin has the ability to restore the proper function of the skin (e.g., DNA repair and cell viability) in both UVAand UVB-irradiated human keratinocytes and dermal fibroblasts [298,299].…”
Section: Apigeninmentioning
confidence: 88%
“…Based on our study, naringin may be a promising antioxidant, which would help relieve oxidative stress and ameliorate OF. Moreover, numerous studies have demonstrated that the expression of core targets including TNF [ 57 ], CASP3 [ 58 ], ESR1 [ 59 ], MMP2 [ 60 ], MMP1 [ 61 ], PPARG [ 62 ], CDKN1A [ 63 ], ACE [ 64 ], etc., plays an important part in regulating oxidative stress. Therefore, we speculated that NG could regulate core targets' expressions and osteoclast differentiation by oxidative stress in OF patients, so as to anti-OF.…”
Section: Discussionmentioning
confidence: 99%